Assessment of Ferroresonance Processes in Schemes of 6-35 kV Electrical Grids on the Basis of Reliability Analysis - Zinoviy Bakhor; Andriy Yatseiko; Roman Ferensovych (Energy Engineering and Control Systems, 2020)
The object of research is the choice of the optimal technical solution to prevent the development or the long existence of ferroresonance processes in electrical distribution grids of 6-35 kV, which are operated in isolated neutral mode. A lot of factors such as the grounding mode of a grid neutral, its capacitive current of a short circuit to the ground, the type and number of voltage transformers (VT) etc. influence on the probability of occurrence and duration of ferroresonance processes. According to the results of the research, the values of capacitive currents of a short circuit to the ground at which stable ferroresonance processes occur in electrical distribution grids of 6-35 kV are determined. The values of capacitive earth fault currents of a grid are decisive for the occurrence of a stable ferroresonance, but the nature of its flow is also influenced by additional accidental factors, such as: a grid voltage, an insulation status of power lines, a load of the secondary winding of voltage transformer etc. Therefore, a model for assessment the frequency of occurrence of a stable ferroresonance process in the electrical grid based on the analysis of the reliability of physical objects in the conditions of external actions was developed. In addition, an algorithm for determining the most dangerous scheme configurations of electrical grids concerning to a VT damage by the frequency of occurrence of a stable ferroresonance process in them and the choice of optimal solutions to prevent the VT damage were proposed.